Using Mobile Learning to Enhance Pre-Service Teachers’ Participation in Distance Education English Tutoring Sessions - Angélica María Carvajal Téllez; Yolanda Duarte Medina (Enletawa Journal, 2018)
This article is the result of a small-scale research study aimed to enhance pre-service teachers’ participation in distance education tutoring sessions at the Universidad Santo Tomas, CAU (University Assistance Centre) in Chiquinquirá. The study was carried out by implementing mobile learning, specifically a mobile learning application called Kahoot. When carrying out online activities, in particular grammar games and oral discussions that involved the use of smart phones in tutorial sessions, the pre- service students were more engaged, and their participation increased greatly. Moreover, it is meaningful for students to improve their English language competence by activating their use of digital skills. Some of the benefits of mobile learning are flexibility and personalized learning activities, which try to address the needs of individual learners. This study showed that mobile learning promotes active participation, as well as knowledge construction and collaborative learning. It also creates a positive atmosphere and exposes students to innovative learning environments.